The power of pulses : saving the world with peas, beans, chickpeas, favas & lentils - Jason, Dan; Eathorne, Alison Malone; Malone, Hilary (Douglas and McIntyre, 2016)
For those who are committed to increasing self-reliance and supporting locally available food sources, pulses are an often-overlooked source of ethical protein. Dan Jason, owner of Salt Spring Seeds, is a long-time advocate of pulses as a healthy and environmentally responsible alternative to meat and tofu. Talented foodie-sister team Hilary Malone and Alison Malone Eathorne collaborate with Jason to create 40+ vegetarian recipes featuring fresh and inventive uses for the garden's bounty, including Broad Bean Succotash with Fresh Ricotta and Poached Eggs on Toast, Crispy Chickpea Power Bowl with Kale, Quinoa and Dukkah Crunch and even Black Bean Brownies with Espresso Ganache. Vibrantly illustrated, this exciting garden-to-kitchen volume is sure to inspire readers to harness the power of pulses.